Disordered eating: The psychometric properties of the Persian version of the Eating Attitudes Test-8 - Esmaeil Mousavi Asl; Sajjad Khanjani; Behzad Mahaki; Youkhabeh Mohammadian (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Disordered eating attitude may lead to full-blown eating disorders. Recent longitudinal studies show that disordered eating attitudes either remain stable or even increase from childhood to adulthood. The current study was done to determine the psychometric properties of the Eating Attitudes Test-8 (EAT-8) and introduce the suitable measure for researchers and therapist in the field of clinical psychology and psychiatrist. MATERIALS AND METHODS: The Persian version of the EAT-8 was produced through forward translation, reconciliation, and back translation. A sample of 302 students were selected through convenience sampling method and completed a set of questionnaires, including the EAT-8, Eating Attitudes Test-16 (EAT-16), Eating Beliefs Questionnaire-18 (EBQ-18), self-esteem scale, and self-compassion scale short-form. The construct validity of the EAT-8 was assessed using confirmatory factor analysis and divergent and convergent validity. Internal consistency and test-retest reliability (2 weeks' interval) were conducted to evaluate the reliability. Data analysis was conducted using SPSS (version 22) software and LISREL (version 8.8). RESULTS: EAT-8 was found to be valid and reliable measures, with good internal consistency and good test-retest reliability among students. In terms of convergent validity, EAT-8 showed a significant positive correlation with self-report measures of EAT-16 and EBQ-18. EAT-8 showed a negative correlation with self-compassion and self-esteem, thus demonstrated a good divergent validity. The results of this study also provide support for the one-factor model of the EAT-8. CONCLUSION: The EAT-8 showed good validity and reliability and could be useful in assessing disordered eating in Iranian population. The EAT-8 shows notable promise as a measure for use in disordered eating research and clinical settings.